Normatividades e instituciones eclesiásticas en el Nuevo Reino de Granada, siglos XVI-XIX - Duve, Thomas; Vogenauer, Stefan (Global Perspectives on Legal History, 2020)
Ecclesiastical institutions and actors were essential for the for-mation of normative orders in early modern Ibero-America. In a series of seminars, organised by the Max Planck Institute for European Legal History in Mexico City, Lima, Bogotá and São Paulo, scholars from different disciplines presented innovative studies on the history of religious normativity and its practices. Based upon the Bogotá colloquium, the present volume fo-cuses on the New Kingdom of Granada (16th - 19th centuries).